THE FEATURES OF MONOPOLISTIC COMPETITION IN THE PHARMACEUTICAL MARKET: GLOBAL AND NATIONAL ASPECTS - BUDNIKEVICH, Iryna; HONCHAR, Vadym (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the peculiarities and specified characteristics of the pharmaceutical market in the concept of monopolistic competition, the design of which allows for the wide use of marketing tools of competition, innovation, research, branding, and others. The specific characteristics that allow identifying the predominant type of competition in the pharmaceutical market as monopolistic competition are summarized. It was noted that certain segments of the pharmaceutical market function within the framework of different market structures: monopoly (manufacturers who own patents for unique medicinal products, individual and collective monopolies in regional markets), oligopoly (manufacturers of certain types of medicinal products, the distribution segment, pharmacy networks of centralized and holding type with a monopoly in the retail sale of medicinal products), monopolistic competition (production and sale of medicinal products). Taking into account the dependence of the national pharmaceutical market on the import of drugs, the state (2018-2022), the competitive situation and generalized forecasts for the growth of the global pharmaceutical market until 2027 were studied. The analysis proved the presence of different factors of market development in each of the studied periods. The high activity of Indian and Chinese companies in developing the global pharmaceutical market was noted. Attention is drawn to the fact that activity in the market of monopolistic competition, especially such an institutionalized one as the pharmaceutical market, requires from participants the competent application of strategic approaches, adaptation of business models, significant investments in R&D and constant production of innovations, establishment of long-term cooperation with partners, optimization of the supply chain, formation systems of constant monitoring and forecasting of the external environment, professional marketing and systemic promotional activities related to traditional and digital elements of the communication mix, network expansion due to permissible regional expansion. It was concluded that the further development of the modern world pharmaceutical market as a structure of monopolistic competition is connected with: acceleration of consumption of medicines in developing countries; expiration of patent protection for a significant number of brand-name drugs; reduction of the market share and profits of branded pharmaceutical companies; legal restrictions on market monopolization; active use of marketing tools to implement non-price competition. The priority factor in increasing the competitiveness of the pharmaceutical market of Ukraine is an effective combination of state and market regulation mechanisms, the successful synthesis of which will contribute to the elimination of disparities between the export and import of medicinal products, reduce the dependence of the Ukrainian pharmaceutical market on foreign supplies of raw materials and finished products, and strengthen the position of domestic manufacturers in foreign markets.